Narrative nursing combined with nostalgia therapy in nursing a typical case of senile paranoid schizophrenia (运用叙事护理联合怀旧疗法护理1例典型老年期偏执型精神分裂症) - YE Junrong (叶君荣); XIAO Aixiang (肖爱祥); HUANG Xingxiao (黄杏笑); YANG Hang (杨航); WU Chenxin (吴晨欣); HE Cuiqiong (何翠琼); WEI Yanheng (魏燕恒); LU Xueling (陆雪玲); CAO Yanyu (曹燕瑜); ZHOU Xiuzhen (周秀珍); TAN Yanfang (谭艳芳) (中西医结合护理)
This paper reviewed the clinical data of a typical elderly paranoid schizophrenia (SP) patient, and experience of narrative nursing combined with nostalgia therapy was summarized. The multi-disciplinary team (MDT) made an assessment and diagnosis at the patient first, and then according to evidence-based search to develop intervention plans, which included drug therapy, physical therapy and rehabilitation and nursing intervention. Specifically, the nursing intervention was mainly about narrative nursing combined with nostalgia therapy. After the intervention, the patient's mental symptoms were effectively controlled, sleep quality and medication compliance were improved. The implementation of narrative nursing combined with nostalgia therapy is potentially effective to improve the mental rehabilitation the SP patient (本文回顾1例典型老年期偏执型精神分裂症(SP)患者的临床资料, 总结叙事护理联合怀旧疗法护理干预措施。通过多学科团队(MDT)评估、诊断, 再根据循证检索制定干预计划, 包括药物治疗, 物理治疗与康复, 护理干预等。老年科特色护理干预包括叙事护理、怀旧疗法和引导式认知训练等。经干预后患者精神症状得到有效控制, 睡眠质量和服药依从性得到改善。叙事护理联合怀旧疗法能够有效促进老年SP患者康复。)